Rational housing bubble - Bo Zhao (Economic Theory, 2015)
This paper studies an economy inhabited by overlapping generations of households and investors, with the only difference between the two being that households derive utility from housing services, whereas investors do not. Tight collateral constraint limits the borrowing capacity of households and drives the equilibrium interest rate level down to the housing price growth rate, which makes housing attractive as a store of value for investors. A housing bubble arises in an equilibrium in which investors hold houses for resale purposes only and without the expectation of receiving a dividend either in terms of utility or in terms of rent. Pension reform that reduces the contribution rate may increase the supply of credit and create the housing bubble. Empirical findings from China are consistent with theoretical predictions. Copyright Springer-Verlag Berlin Heidelberg 2015
Keywords: Chinese economy; Collateral constraint; E20; G12; Housing bubble; Pension reform; R21